THE DISTRIBUTION AND ABUNDANCE OF TOXIC BENTHIC DINOFLAGELLATES IN MALANG RAPAT COASTAL WATERS OF BINTAN ISLAND, KEPULAUAN RIAU - Nurrachmi, Irvina; Amin, Bintal; Andini, Dilla; Afriansyah, M.; Anadri, Rifqi Rafif (Asian Journal of Aquatic Sciences, 2023)
This research was conducted in May - June 2018 by surveying and taking a sample from Malang Rapat water on the East Coast of Bintan Island, Kepulauan Riau to determine the abundance and distribution of toxic benthic dinoflagellates associated with seaweed (Sargassum sp) and seagrass (Enhalus accoroides). Samples were taken from four sampling locations which were carried out purposively by taking into account the different anthropogenic activities that occurred in each region. The results of the study found 3 genera of toxic benthic dinoflagellates, namely Gambierdiscus sp, Ostreopsis sp, and Prorocentrum sp. The highest abundance of toxic benthic dinoflagellates associated with Sargassum sp was found in station 3, which was 302.279 cells/g, and the lowest at station 4 with (133.529 cells/g), while E. accoroides has the highest abundance at station 1 which was 620.65 cells/g). The abundance of toxic dinoflagellates in Sargassum sp has a positive correlation with nitrate concentration, but on the contrary, it was negatively correlated with the concentration of nitrate and phosphate in these waters to E. accoroides. The measured water quality parameters were still within the tolerance range for the marine organism. Further research is still needed to answer the cause of these differences and whether there are any fluctuations of abundance and the specific appearance of the toxic dinoflagellate.